Ape's great escape - Punter, Rusell; Semple, David; Tyler, Jenny (London : Usborne Publishing Ltd., 2018)
Ape's in chains for stealing grapes. He has a cunning scheme to escape, but will the prison guards catch him? Find out in this entertaining story for beginner readers, with simple rhyming text and stylish illustrations throughout. A delight to share with very young children, and with parents notes on phonics at the back of the book.
Keywords: Apes -- Juvenile fiction; Children's stories; Reading -- Phonetic method -- Juvenile fiction